Effect of synthesized Ag nanoparticles by using the different amounts of polyvinylpyrrolidone for Ag-natural rubber hybrid sheets and their antibacterial properties - Prasanseang, Warot; Sriwong, Chaval; Choojun, Kittisak (My University, 2017)
Ag-natural rubber (Ag-NR) hybrid sheets were successfully prepared with a very simple and low cost method. In this method, silver nanoparticles (AgNPs) were firstly synthesized by a rapid and green microwave-assisted using polyvinylpyrroridone (PVP) media. The effect of PVP weight ratios towards the size of AgNPs was also investigated. Then, Ag-NR hybrid sheet samples were prepared by latex mixing-casting method using concentrated natural rubber (NR) latex with the synthesized AgNPs colloids. The characteristic absorption, particles sizes and shapes of the obtained AgNPs were examined through UV-vis, TEM and SAED. Also, the prepared Ag-NR sheet samples were characterized using XRD, FT-IR, SEM and EDS techniques. It was found that the particles sizes of all the synthesized AgNPs had spherical-like shape, and the mean sizes were increased from 29.7 to 90.4 nm upon increasing PVP contents. EDS results showed the AgNPs were well-dispersed and impregnated into the rubber matrix. Moreover, the antibacterial properties of the prepared Ag-NR sheets were tested by agar disk-diffusion method with Gram-positive and Gramnegative bacteria as Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli), respectively. The results showed that the hybrid sheets exhibited excellent antibacterial properties against these bacteria, in which the zones of inhibition were also dependent on the synthesized AgNPs by utilizing the different amounts of PVP.
Keywords: Antibacterial properties; Latex mixing-casting process; Microwave-assisted method; Natural rubber hybrid sheet; Silver nanoparticles (AgNPs)